Sin City an adult entertainment hub - Aban, Maria Kristina C.; Ozaeta, Emilio U. (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
Sin City : an adult entertainment is a study on sexually-oriented business establishments and its acceptance in the Filipino context. This study aims to analyze what sexually-oriented businesses (SOBs) may be done in the Philippines within the grounds of the law and how they may be designed architecturally to become safe and secure environments for sexually-oriented businesses. The study also seeks to have sex and eroticism accepted and normalized by the Filipinos so that they can be more educated in the topic, and still respecting the sensitivity of the Filipinos regarding privacy and humility. Not only does this study contribute to having a more accepting culture and a more educated society,it is mostly significant as it aims to protect those who are or have been exploited in this line of business. Instead of frowning upon those who make a living through sexually-oriented businesses, it is better that they be given adequate working environments to carry out activities. It shall focus on the top two most common SOBs in the Philippines, strip clubs and motels, while also giving attention to commercial and retail-type SOBs. Additionally, it shall also relay sex education and appreciation through an architectural structure common used especially for these goals, a museum. The study aims to encourage people to learn, explore, and be free to do what they want, and for them to prove what regulated sexually-oriented businesses can be.
Includes appendices
Includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Sex-oriented businesses -- Philippines; Sin City (Sex-oriented businesses).